PEREMPUAN DALAM WACANA POLITIK ISLAM - Hulwati Hulwati (Universitas Islam Negeri Imam Bonjol Padang, 2012)
Talk about women in Islamic studies became more prevalent and warmed up, it even looks that this study has never lost its appeal. All activities are highlighted in the context of modern life, because in some of them there are only dropped as a housewife (domistic-worker). But became a career woman and even plunge into politics, so this statement has invited some controversial comments. Based on the problems described above, this paper will not examine all aspects of the women in the Islamic view, but this discussion will focus on how the position of women in Islamic political debate, it is precisely this paper tries to reveal how the movement of women seen from the eyes of political Islam, the reveals some important points, such as women in Islam, the position of women in Islamic politics and the last of this section described the reality of women in the social world. Keywords : Women and Islamic political debateCopyright © 2012 by Kafa`ah All right reservedDOI : 10.15548/jk.v2i1.42